Identifying Poor Performance Dimensions And Clustering Poor Performers: A Case Study In Tehran University Of Medical Sciences - Seyed Mohsen Tabatabaei; Masumeh Habibi Baghi; Seyedeh Bahareh Kashian; Mahmood Biglar (پیاورد سلامت, 2016)
Background and Aim: Employees are an organizationchr('39')s greatest assets and organizational performance is dependent to employee’s performance. Presence of inefficient employees can make other employees to be less productive. To improve inefficient employees to high performance level, it is necessary to analyze the performance of employees. This study aims to identify and determine poor performance dimensions and cluster inefficient staffs.